Depression among university counseling students - Arezi, Musaab; Zainel, Anfal Abdulhafedh (Journal of Indonesian Psychological Science (JIPS), 2025)
The aim of this study was to examine the level of depression among students of the University of Duhok, College of Basic Education, and to measure potential variation based on gender and year of study. Utilizing a descriptive correlational research approach, information was collected from a stratified random sample of 60 students, with 30 males and 30 females evenly distributed across second and fourth years of study. The researchers used the Patient Health Questionnaire (PHQ-9), a psychometrically validated depression screening instrument that is supported. Statistical analysis revealed that counseling students exhibited depression levels significantly above average. No statistically significant differences were found between male and female students, which suggests both experience similar psychological challenges in this academic environment. However, wide differences emerged based on academic progress, with second-year students reporting significantly more depression than fourth-year students. Further analysis revealed differences between some of the depression symptoms in terms of academic year and described the distribution of students by level of clinical depression. These findings indicate that vulnerability to depression may decrease as students’ progress through their academic program, possibly as a function of improved academic adjustment, improved coping capacity, and more consolidated professional identity. These results highlight the importance of implementing targeted psychological support programs in counseling for advising students, particularly during the early academic years, and have implications for understanding the developmental process of mental health in future counseling professionals. KEY WORDS: depression; counseling students; PHQ-9; Duhok; mental health Copyright ©2025. The Authors. Published by Journal of Indonesian Psychological Science (JIPS). This is an open access article under the CC BY NO SA. Link: Creative Commons — Attribution-NonCommercial-ShareAlike 4.0 International — CC BY-NC-SA 4.0